Neighbourhood Satisfaction Among Municipal Tenants in the Helsinki Metropolitan Area - Rosengren, Katriina; Kauppinen, Timo M. (Scandinavian University Press, 2025)
This article analyses municipal tenants’ neighbourhood satisfaction (NS) in the Helsinki metropolitan area. If social mixing has managed to equalise differences related to the residential environment across different social groups, perceived neighbourhood conditions among tenure groups should be similar. We know, however, that even in a Nordic capital with a conscious and long-term effort at small-scale mixing, social housing is not geographically spread out evenly and that clustering of social tenants occurs. We also know that objective resources among social tenants are lower than in other tenures, contributing to subjective wellbeing, of which NS is a component. We examine the Helsinki metropolitan area’s objective and subjective neighbourhood conditions using a large residential survey and national register data. Our results show that neighbourhood amenities and locational characteristics do not differ across tenure groups in the Helsinki metropolitan area – however, tenants in municipal social housing report lower NS than other tenure groups. Social mixing appears to promote spatial justice at the neighbourhood level better than it has managed to equalise differences in subjective experiences across tenure groups. This study contributes to understanding NS as a component of subjective wellbeing. It also highlights the unequal distribution of social housing in the Helsinki metropolitan area, which we see as a risk for accelerating segregation across tenure groups. Differences in perceived satisfaction with neighbourhood across tenure groups may reflect differences in micro-scale environments, suggesting a need for policies improving spatial justice at a sub-neighbourhood or residential level.